Risk Factors for Development of Rhegmatogenous Retinal Detachment in Patients with Uveitis - Paradee Kunavisarut (2018)
© 2018, Taylor & Francis. All rights reserved. Purpose: To describe risk factors for development of rhegmatogenous retinal detachment (RRD) in patients with uveitis. Methods: We performed a retrospective review of 411 consecutive human immunodeficiency virus-negative patients with uveitis (571 affected eyes) and report on prevalence, risk factors and visual outcomes of patients with RRD. Results: Prevalence of RRD was 7% of all patients with uveitis. Multivariate analysis revealed that posterior uveitis and panuveitis were associated with RRD (P = 0.001). Strong association between RRD development and infectious uveitis was also observed (P = 0.009). Acute retinal necrosis (ARN) was firmly associated with RRD development (P = 0.016). Although anatomical success was obtained, functional outcome was poor. Poor visual outcomes at 6-month and 1-year follow-up were associated with initial VA < counting fingers (P = 0.05, P = 0.044). Conclusions: Prevalence of RRD in uveitis was 7% and development of RRD was encountered in posterior and panuveitis. Infectious uveitis (specifically ARN) formed a high risk for RRD.